Implementasi Manajemen Bandwidth Simple Queue Sebagai Optimalisasi Layanan Jaringan Internet Warga Menggunakan Metode NDLC - Miftahur Rahman; Moh. Dasuki; Hardian Oktavianto (Universitas Muhammadiyah Riau, 2024)
Krajan Hamlet, one of the areas in Jember Regency, has built an RT-RW Net network which aims to make it easier for the community or residents there to use the internet network for education, work and so on at relatively low costs. However, there is a problem, namely that using the internet network often causes buffering and even the network goes down if used simultaneously because the bandwidth is not limited to each user or client. The solution is to carry out simple queue bandwidth management. The completion steps in this research use the Network Development Life Cycle (NDLC) method. Resulting in research that the simple queue bandwidth management that has been carried out can be applied to the RT/RW Net network infrastructure that has been built, it was proven that when conducting bandwidth testing there was no bandwidth that exceeded the maximum limit that had been determined, namely the 20 Mbps bandwidth provided by the ISP divided into 5 Mbps for the Admin and for each client, they get a bandwidth of 3 Mbps, and when testing the network quality based on QoS calculations it can be categorized as good.